Mass transfer kinetics and quality evaluation of tomato seed oil extracted using emerging technologies. (January 2023) - Kumar, Sumit; Nirmal Thirunavookarasu, S.; Sunil, C.K.; Vignesh, S.; Venkatachalapathy, N.; Rawson, Ashish
Abstract: The Present study was conducted to extract tomato seed oil using emerging technologies which include moderate electric field (MEF), low temperature microwave (MW), radio-frequency (RF), power ultrasound (US) and combined low temperature microwave-power ultrasound (MWUS) at different solid to liquid (S/L) ratio and power level. A green solvent (ethanol: ethyl acetate) was used to extract the oil from tomato seed and a mass transfer kinetic study was studied to find the extraction kinetics and effect of different treatments. MWUS assisted extracted oil was observed to have the highest extraction yield (23.07%) as well as the best quality of oil extracted. The extracted oil using MWUS treatment was mainly composed of PUFA (Linoleic acid), MUFA (Oleic acid) and Stearic acid. Low temperature microwave-ultrasound assisted extraction (MUAE) increased the linoleic, stearic and oleic acid content by 30.91, 5.16 and 7.29% respectively in tomato seed oil composition compared to the conventional Soxhlet extraction (SXE) method. Industrial relevance: The novel 'Low temperature microwave-ultrasound assisted extraction (MUAE)' technology presents a promising result combination of emerging technology for the extraction of oil. The impact of low temperature dipole moment of microwave followed by low intensity ultrasound cavitation leads to the breakdown of the tomato seed matrix. Further, this combination improved the extraction yield although the solvent used very lower solubility compared to conventional solvents. The quality of the extracted oil following MUAE technology was found to be much better than conventional extraction. Hence this combination presents a good scope for application in the food industry, with good commercial value and being environmentally friendly makes it more acceptable. Graphical abstract: Graphical Abstract Unlabelled Image Highlights: RAE, MAE and MUAE is proposed first time for tomato seed oil extraction. MUAE treatment recovered higher unsaturated fatty acid content. MUAE treatment had highest oil yield and retained oil quality. Oil extraction kinetics was well explained by Fick's law of diffusion.